Dynamic evolution of keyhole during multi-pulse drilling with a millisecond laser on 304 stainless steel. (August 2022) - Zhang, Yue; He, Xiuli; Yu, Gang; Li, Shaoxia; Tian, Chongxi; Ning, Weijian; Zhang, Yanmei
Highlights: Due to the Gaussian distribution of laser beam, the ejection efficiency changes during the evolution of keyhole. The multi-pulse drilling process are divided into rapid, linear, and moderate periods. A three-dimensional numerical model is developed with considering three driving forces of molten pool. The melt flow transition and its influence factors are investigated. Abstract: The efficiency of millisecond laser drilling is high due to the molten material ejection, and is applied in many industries like aerospace, automobile and electronics. However, there may be some defects such as hole blockage, low machining accuracy and low repeatability, especially for the process of multi-pulse drilling. The melt flow remaining inside keyhole due to inefficient ejection, is responsible for the formation of those defects. Hence, it is necessary to investigate the dynamic behavior of melt flow during multi-pulse drilling. In this paper, the dynamic evolution of keyhole is investigated combining in-situ observation and numerical simulation methods. According to the ejection efficiency, the multi-pulse drilling process can be divided into three periods, namely rapid drilling period, linear drilling period, and moderate drilling period. The melt flow behaves differently in each period. In rapid drilling period, a conical keyhole is formed in the end. The melt flow behavior is affected dominantly by the recoil pressure when the laser is on and by the surface tension when the laser is off. In linear drilling period, the blocked keyhole occurs occasionally. The melt flow behavior is affected by gravity and recoil pressure when the laser is on and by the surface tension and recoil pressure when the laser is off. In moderate drilling period, the keyhole profile is wavy. The melt flow behavior is affected by surface tension and recoil pressure dominantly during the whole period. The melt flow transition and its influence factors are investigated in this paper, which is helpful for understanding the physical processes during the multi-pulse laser irradiation process.